2013
DOI: 10.1134/s086986431304001x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of channel orientation on heat transfer and wall shear stress in the bubbly flow

Abstract: Experimental investigations of heat transfer from the heated wall to the two-phase bubbly flow were performed in vertical annular channel using air-water system. The IR-thermography and miniature temperature sensors were used to measure heat transfer coefficients. The influence of bubbles on heat transfer is shown in comparison with the case of single phase flow. The presence of bubbles in the flow leads to heat transfer intensification in the annular channel even for low void fractions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…Intensification of the heat transfer in this region relates to the additional flow turbulisation by bubbles and the reorganisation of the liquid velocity profile which leads to the increase of the velocity gradient in the near wall region. Early a similar degree of the increasing of wall shear stress and heat transfer coefficient in turbulent two-phase bubbly flows was found in [40,41].…”
Section: Discussionsupporting
confidence: 69%
“…Intensification of the heat transfer in this region relates to the additional flow turbulisation by bubbles and the reorganisation of the liquid velocity profile which leads to the increase of the velocity gradient in the near wall region. Early a similar degree of the increasing of wall shear stress and heat transfer coefficient in turbulent two-phase bubbly flows was found in [40,41].…”
Section: Discussionsupporting
confidence: 69%
“…For experimental studies of heat transfer from the heated wall to the bubble flow, we used the test section, made of thin-walled stainless steel [7] (Fig. 1 b).…”
Section: Methodsmentioning
confidence: 99%
“…For the case of laminar natural convection it has been found that the injection of sub-milimeter bubbles enhances the heat transfer due to mixing and advection effects (Kitagawa and Murai, 2013). This effect is maximized when bubbles impact and slide along hot walls (Donnelly et al, 2009 in vertical and inclined channels have shown that for high void fraction of gas and low friction Reynolds numbers the effect on the heat transfer coefficient and the wall shear stress are strongly dependent on the inclination angle (Kashinsky et al, 2013(Kashinsky et al, , 2014. In the present work, the dependency of the flow and the heat transfer in low void fraction bubbly flows on the inclination angle of a channel are studied using direct numerical simulations.…”
Section: Introductionmentioning
confidence: 95%